Mind Mapping Solutions to Improve Learning Outcomes in Islamic Education and Natural Sciences - Sari, Julita Permata; Sukandar, Warlan; Yumna, Yumna; Nurhasanah, Nurhasanah; Dahliana, Dina; Yolanda, Sylvi Aulia; Cahyani, Rahmi Indah (Sekolah Tinggi Agama Islam Solok Nan Indah, 2024)
Mind mapping is a method that can be used in learning natural and social sciences. In fact, this research aims to explain the planning, implementation and improvement of learning outcomes in Islamic education and natural sciences using the mind map method. This research uses classroom action research methods. The research subjects were all 7 class V students consisting of four boys and three girls. Data sources were obtained from teachers and fifth grade students using observation and tests. Data were analyzed through four steps, namely the planning stage, action stage, observation and reflection stage. The results of the research showed that there was an increase in the average student score from cycle I of 66.42, then increased to 85.00 in cycle II and student success was seen to increase from cycle I, 42.85% of students completed, while in cycle II this occurred. enhancement. Complete learning outcomes were 85.71%. For this reason, it is recommended that teachers use the mind map method in science learning and create a comfortable learning atmosphere so that children are interested and do not get bored easily when studying.